Open Dialogue as a Human Rights-Aligned Approach - von Peter, Sebastian; Aderhold, Volkmar; Cubellis, Lauren; Bergström, Tomi; Stastny, Peter; Seikkula, Jaakko; Puras, Dainius (Frontiers in Psychiatry, 2019)
Throughout the last 20 years, the human rights perspective has increasingly developed into a paradigm against which to appraise and evaluate mental health care. This article investigates to what extent the Finnish Open Dialogue (OD) approach both aligns with human rights and may be qualified to strengthen compliance with human rights perspectives in global mental health care. Being a conceptual paper, the structural and therapeutic principles of OD are theoretical-ly discussed against the background of human rights, as framed by the Universal Declaration of Human Rights, the UN Convention on the Rights of People with Disabilities, and the two recent annual reports of the Human Rights Council. It is shown that OD aligns well with dis-courses on human rights, being a largely non-institutional and non-medicalizing approach that both depends on and fosters local and context-bound forms of knowledge and practice. Its fundamental network perspective facilitates a contextual and relational understanding of men-tal-wellbeing, as postulated by contemporary human rights approaches. OD opens the space for anyone to speak (out), for mutual respect and equality, for autonomy, and to address pow-er differentials, making it well suited to preventing coercion and other forms of human rights violation. It is concluded that OD can be understood as a human rights aligned approach.